Manipulating Myc for reparative regeneration - Ascanelli, Camilla; Dahir, Rowda; Wilson, Catherine H. (Frontiers in Cell and Developmental Biology, 2024)
The Myc family of proto-oncogenes is a key node for signal transduction of external pro-proliferative signals to the cellular processes required for development, tissue homeostasis maintenance and regeneration across evolution. The tight regulation of Myc synthesis and activity is essential for restricting its oncogenic potential. In this review, we highlight the central role Myc plays in regeneration across the animal kingdom (from cnidaria to echinoderms, to chordata) and how Myc could be employed to unlock the regenerative potential of non-regenerative tissues in humans for therapeutic purposes. Mastering the fine balance of harnessing the ability of Myc to promote transcription without triggering oncogenesis may open the door to many exciting opportunities for therapeutic development across a wide array of applications.